TRACKING TECHNIQUES AND TREATMENT METHOD USING CPU ASSEMBLING - Adhi Susanto; Ir. Irwan Nimara, MM (Jurnal Sistem Komputer, 1998)
The damage that occurs on a computer mostly due to the age of the components thatshould be replaced and the human error factor in treatment procedures and the use ofcomputer or electronic components.Generally in this method, a person who wants to repair the damage on theircomputers can easily understand and practice it.